2019
DOI: 10.1044/2019_pers-sig17-2019-0005
|View full text |Cite
|
Sign up to set email alerts
|

Speech-Language Pathology in Malaysia: Perspectives and Challenges

Abstract: Purpose Malaysia, with its diverse culture and multilingual population, presents a unique and interesting setting for working as a speech-language pathologist (SLP). This article discusses the challenges that SLPs face when providing speech and language therapy in Malaysia and issues that need to be addressed for continued growth of this profession. While providing suggestions to SLPs on methods to overcome the challenges faced and improve their clinical practice, this article also calls upon inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…One of the main limitations in this study is that almost all of our participants were recruited from an online support group (92.7%), indicating that most of these parents had prior knowledge and support in caring for a child with ASD. Future studies should consider recruiting parents from a wide range of sources, including hospitals and community‐based service centres, in order to reach a wider audience with varied education and income levels (Chu, Khoong, Mohamad Ismail, Altaher, & Razak, 2019; Chu & Tan, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…One of the main limitations in this study is that almost all of our participants were recruited from an online support group (92.7%), indicating that most of these parents had prior knowledge and support in caring for a child with ASD. Future studies should consider recruiting parents from a wide range of sources, including hospitals and community‐based service centres, in order to reach a wider audience with varied education and income levels (Chu, Khoong, Mohamad Ismail, Altaher, & Razak, 2019; Chu & Tan, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Speech and language therapy services are sparse in these countries. For example, in Sub-Saharan Africa, there was a ratio of 0-6 speech and language therapists per million population (Jochmann 2006, Mulwafu et al 2017, Wylie et al 2012 and similar limitations can be found in Asia and other parts of Africa (Cheng 2010, Chu et al 2019, Haas 2015, Pillay et al 2020. Many of the Sub-Saharan African countries have no training programmes for SLTs (Mulwafu et al 2017).…”
Section: Social Inequalities In the Receipt Of Health And Social Carementioning
confidence: 96%
“…2012) and similar limitations can be found in Asia and other parts of Africa (Cheng 2010, Chu et al . 2019, Haas 2015, Pillay et al . 2020).…”
Section: Social Inequalities In the Receipt Of Health And Social Carementioning
confidence: 99%
See 2 more Smart Citations